Biomechanical Analysis of Jump Smash in Badminton Athletes - Muhammad Rafi; Alimuddin; Ahmad Chaeroni; Fahd Mukhtarsyaf (STKIP Pasundan, 2026)
This study aimed to analyze the biomechanics of jump smash techniques in badminton athletes at PB Polda Sumbar. A descriptive quantitative method with a biomechanical analysis approach was used. The participants were badminton athletes selected purposively based on their active involvement in training sessions. Data were collected through observation and video recordings of jump smash movements. The analysis focused on body posture, joint angles, movement coordination, and landing balance. The results showed that effective jump smash performance was influenced by proper body coordination, optimal knee flexion during take-off, arm swing speed, and body balance during landing. Athletes with better biomechanical movement patterns produced stronger and more accurate smashes. In conclusion, proper biomechanical techniques play an important role in improving jump smash effectiveness and overall badminton athlete performance.